The New Crisis of Increasing All-Cause Mortality in US Children and Adolescents - Woolf, Steven H; Wolf, Elizabeth R; Rivara, Frederick P (JAMA : the journal of the American Medical Association, 2023)
This Viewpoint discusses increased rates in pediatric mortality by age and cause between 1999 and 2021.